Broader head, stronger bite: In vivo bite forces in European eel Anguilla anguilla - J. De Meyer; A. Herrel; C. Belpaire; G. Goemans; C. Ide; B. De Kegel; J. Christiaens; D. Adriaens (Journal of Fish Biology, 2018)
This work examined three different phenotypes of the yellow‐eel stage of the European eel Anguilla anguilla , broad‐heads, narrow‐heads and eels with an intermediate head shape. The aim was to see whether broad‐headed A. anguilla , which generally consume harder, larger prey, such as crustaceans and fish, exerted greater bite force than the narrow‐headed variant, which mainly consume soft, small prey such as chironomid larvae. It was found that in 99 yellow A. anguilla , in vivo bite force of broad‐heads are higher compared with narrow‐heads and intermediates.

Morphological Deformities in Chironomus Riparius Meigen Larvae after Exposure to Cadmium over Several Generations - L. Janssens de Bisthoven; J. Postma; A. Vermeulen; G. Goemans; F. Ollevier (Water, Air, & Soil Pollution, 2001)

Sudan-β- d -glucuronides and their use for the histochemical localization of β-glucuronidase activity in transgenic plants - E. Van der Eycken; N. Terryn; J. L. Goeman; G. Carlens; W. Nerinckx; M. Claeyssens; J. Van der Eycken; M. Van Montagu; M. Brito-Arias; G. Engler (Plant Cell Reports, 2000)